Cultural Influences on Public-Private Partnerships in Global Governance - Masters, Adam B. author. aut Link
XV, 313 p. 8 illus.
Keywords: This book explores how professional and organisational cultures influence global public-private partnerships, which form a key element of global governance. Using case studies, the partnerships of three international government organisations – the International Telecommunication Union, Interpol and the International Centre for the Study of the Preservation and Restoration of Cultural Property – illustrate how partnerships are formed and operate in accordance with the accepted cultural beliefs, values and values associated with both profession and organisation. In brief, engineers create partnerships they are comfortable with, which are different in form and operation to those of police, which also differ from those of the conservator. This book will appeal to scholars of International Relations, global governance, organisational studies and public administration. It also conveys lessons for professionals at the international level in international government organisations, business andcivil society who engage in, or want to engage in global public-private partnerships. Adam B. Masters holds a post-doctoral fellowship in the Research School of Social Sciences at the Australian National University (ANU). He is Deputy Director Governance of the Transnational Research Institute on Corruption, based at the ANU in Canberra, Australia. Dr Masters' research focuses on organised crime and corruption.